Development of Methodic Approach to Construction of Recombinant Strain, Producer of the Cholera Toxin B Subunit - D. S. Yanov; S. N. Klinova; A. V. Mironin; I. V. Zhivov; I. P. Pogorelsky; V. I. Drobkov; Yu. N. Feodorov; Ya. A. Kibirev (Проблемы особо опасных инфекций, 2010)
Presented are the results of experiments on the construction of Escherichia coli Top10 (pTrcSuB) strain, perspective for the development of recombinant cholera vaccine for peroral use. The obtained strain possesses inducible expression of cholera toxin B subunit. Peculiarities of cloned gene expression in strain-producer and the conditions of its maintaining were studied. The proposed approach will allow to obtain effective and safe cholera vaccines.